Sygdommen satte spor i os. Den pårørendes afsøgning af kropslige grænser og identitet i Hanne Ørstaviks Ti Amo (2020) og Amalie Smiths I CIVIL (2012) - Dall, Sidsel Boysen (Folia Scandinavica Posnaniensia, 2024)
Caring, writing and the desire for knowledge are deeply intertwined phenomena in Amalie Smith’s poetry collection I CIVIL and Hanne Ørstavik’s novel Ti Amo, both of which portray women in romantic relations with men who are cancer patients. Through depictions of the women’s initial attempts to maintain the closeness to their partners, the books explore the relational and somatic borderland between symbiosis and separation from the perspective of two informal caregivers. Taking a Lacanian approach, this borderland can be understood as a passage from the symbolic to the real which the women gain access to through their intense desire for knowledge and bodily experiences of jouissance and abjection. As informal caregivers for men who are unlikely to survive their illness, the women experience conflicting relational desires for both intimacy and distance. This article investigates how the passage from the symbolic to the real reintroduces the women to relational challenges from an early developmental stage and thus helps them solve the aforementioned conflict.